INTERACTIONS OF SHORT-TERM AND LONG-TERM INTEREST RATES IN MALAYSIAN DEBT MARKETS: APPLICATION OF ERROR CORRECTION MODEL AND WAVELET ANALYSIS - Abdul Razak Abdul Hadi; Zalina Zainuddin; Hafezali Iqbal Hussain; Raja Rehan (Asian Academy of Management Journal, 2019)
The study examines the key determinant of short- and long-term interest rates within the framework of term structure of interest rate theory. The study employs both error correction model (ECM) and wavelet analysis on these two important economic variables. Using time series data from January 2005 through April 2017, the empirical findings from long-run regression show there is a significant negative relationship between the short- and the long-term interest rates. The two variables are also found to be negatively correlated. More importantly, the statistical results from the ECM at lag 2 reveal that there is a significant long-term relationship between short- and long-term interest rates. Therefore, this empirical finding is in line with the notion of interest rate expectation theory.